‘설향’ 딸기의 토경 육묘에서 칼슘 시비가 모주의 생장, 생리장해 발현, 및 자묘 발생에 미치는 영향 - 최종명(Jong Myung Choi); 남민호(Min Ho Nam); 이희수(Hei Soo Lee); 김대영(Dae-Young Kim); 윤무경(Moo Kyung Yoon); 고관달(Kwan Dal Ko) (Weon'ye gwahag gi'sulji, 2012)
The Ca deficiency is a serious problem in the propagation of domestically bred 'Seolhyang' strawberry through soil cultivation. The objective of this research was to investigate the impact of the Ca containing fertilizers on the decrease of Ca deficiency symptoms and in the growth of mother and daughter plants. To achieve this, chemicals of 1.125 mM $Ca(OH)_2$, 0.375 mM $MgCl_2$, and 1.25 mM KCl were blended to contain the K:Ca:Mg (4:2:1) and the influence was compared to a commercial fertilizer, Azuro-Calma ($NO_3$-N 13%, $K_2O$ 1%, CaO 16%, MgO 6%), when those were applied as solutions with the electrical conductivity (EC) controlled to 0.6 or 1.0dS ${·}m^{-1}$. During 120 days after transplant, the Azuro-Calma was more effective than the combined fertilizer in the reduction of mother and daughter plants on which Ca deficiency was appeared. The application of two Ca containing fertilizers resulted in the heavier fresh and dry weights of mother plants. The treatments of 1.0dS ${·}m^{-1}$ of two fertilizers were more effective than those of 0.6dS ${·}m^{-1}$. The combined fertilizer was also more effective than Azuro-calma on the growth of above ground plant tissue. The results in length, fresh and dry weight of runners occurred from a mother plants showed that the treatment of 1.0dS ${·}m^{-1}$ of combined fertilizer was most effective followed by those of 1.0dS ${·}m^{-1}$ of Azuro-Calma, 0.6dS ${·}m^{-1}$ of combined fertilizer, 0.6dS ${·}m^{-1}$ of Azuro-Calma, and control. The fresh weights of daughter plants were heavier in the treatments of Ca application than those in the control treatment, but the differences between 0.6dS ${·}m^{-1}$ and control were not significant. The above results indicate that Azuro-Calma is more effective in decreasing plants showing the Ca deficiency symptoms. However, the combined fertilizer of K:Ca:Mg is more desirable when we are concerned about the decrease of crops showing Ca deficiency as well as increase of the growth in above ground plant tissue. 국내에서 육성된 '설향' 딸기에서 칼슘결핍 증상이 빈번하게 발생하고 육묘 시 모주의 생육 저하, 자묘 채취량 감소 및 자묘 품질저하의 원인이 되어왔다. 따라서 단일 비료를 조합하여 K, Ca 및 Mg이 4:2:1의 비율이 되도록 조절한 비료 또는 상업용으로 시판되는 Azuro-Calma를 0.6dS ${·}m^{-1}$ 또는 1.0dS ${·}m^{-1}$로 조절하여 토양에 관주처리할 경우 모주 생육 및 자묘 발생에 미치는 영향을 구명하기 위하여 본 연구를 수행하였다. 정식 후 120일 동안 무처리구에 비해 모든 칼슘 비료 시비구에서 칼슘 결핍증상이 발현된 모주 수가 뚜렷하게 감소하였으며 본 연구의 조합비료보다 Azuro-Calma의 효과가 우수하였다. 무처리구에 비해 모든 칼슘 비료 시비구에서 모주의 생체중과 건물중이 무거웠다. 또한 두 종류 비료 모두 0.6dS ${·}m^{-1}$ 처리보다 1.0dS ${·}m^{-1}$로 시비 농도를 높일 경우 지상부 생장량이 많았고, 본 연구의 혼합 비료가 Azuro-Calma보다 지상부 생체중과 건물중 증가에 더 효과적이었다. 혼합비료 1.0dS ${·}m^{-1}$ 처리에서 가장 긴 런너 길이를 보였고, Azuro-Calma 0.6dS ${·}m^{-1}$ 처리는 무처리구와 비슷한 경향을 보였다. 런너의 생체중과 건물중 역시 혼합비료 1.0dS ${·}m^{-1}$ 처리에서 가장 무거웠으며 Azuro-Calma 1.0dS ${·}m^{-1}$ 처리에서도 생육이 우수하였다. 무처리구보다 칼슘 시비구에서 자묘의 생체중이 더 무거웠지만 칼슘을 시비한 처리중에는 Azuro-Calma 0.6dS ${·}m^{-1}$ 처리가 가장 가벼웠다. 이상과 같은 결과는 Ca와 Mg이 주요 구성 성분인 Azuro-Calma가 칼슘 결핍 증상을 감소시키기에는 더 효과적이지만 K:Ca:Mg의 비율을 조절하여 세 종류 비료를 동시에 시비하는 것이 칼슘 결핍증상 억제와 모주 및 자묘의 생장량 증가에 효과적이라고 판단한다.